The Influence of Principal's Authentic Leadership and Work Climate on Teachers' Social Competence at SMKN 1 Kuantan Mudik - Darmayanti, Suci; Bunari , Bunari; Isjoni , Isjoni (CV. Tripe Konsultan, 2024)
This study aims to determine the influence of (1) the principal’s authentic leadership and (2) the work climate on (3) teachers’ social competence at SMKN 1 Kuantan Mudik. This research adopts a quantitative approach with a random sampling technique, meaning the samples are selected randomly. The data collection method used in this study is a questionnaire. The results indicate an influence of teachers' social competence on teachers' social competence. The partial hypothesis test shows a significance value of 3.507. By comparing the calculated t-value and the t-table value (3.507 > 1.671), the hypothesis is accepted. The conclusion is that since the calculated t-value (3.507) is greater than the t-table value (1.671) and the significance level is less than 0.05 (0.001 < 0.05), it means that ????a is accepted, and ????0 is rejected. This implies that, partially, there is a significant influence of the principal’s authentic leadership on teachers’ social competence at SMKN 1 Kuantan Mudik. Furthermore, there is also an influence of the work climate on teachers’ social competence. The partial hypothesis test results show a significance value of 4.039. By comparing the calculated t-value and the t-table value (4.039 > 1.671) and noting that the significance level is less than 0.05 (0.000 < 0.05), it means that ????a is accepted, and ????0 is rejected. This indicates that, partially, there is a significant influence of the work climate on teachers’ social competence. The combined influence of the principal’s authentic leadership and the work climate is measured at (3.150), as the calculated F-value (33.690) is greater than (3.150), and the significance level (0.000) is less than 0.05. Therefore, ????0 is rejected, and ????a is accepted. This demonstrates a significant influence of the principal’s authentic leadership and the work climate on teachers’ social competence at SMKN 1 Kuantan Mudik.